Produksi Permen Jelly Cokelat Edamame dengan Perlakuan Rasio Penambahan Gelatin dan Bubuk Konjak - Vanindya Rachma Febrilyana (Fakultas Teknologi Pertanian, 2025)
Functional jelly candy is a type of soft confectionery product with a chewy texture and high nutritional potential. This study aimed to determine the effect of the ratio of gelatin and konjac powder on the organoleptic and chemical characteristics of chocolate-edamame jelly candy. A completely randomized design (CRD) with two factors was used, consisting of gelatin concentrations (8%, 10%, and 12%) and konjac powder concentrations (1%, 3%, and 5%) in 9 treatment combinations. The parameters observed included organoleptic tests (color, aroma, taste, texture, and overall preference), moisture content, antioxidant activity (DPPH method), and protein content (Kjeldahl method). The results showed that the A3B1 treatment (12% gelatin and 5% konjac) was the most preferred based on the highest organoleptic scores and overall effectiveness value, with a moisture content of 15.78% and a protein content of 14.81%. The highest antioxidant activity was found in the A1B3 treatment (8% gelatin and 1% konjac), reaching 43.60%, although it was less favored by the panelists. Statistical analysis revealed that the ratio of gelatin and konjac powder had a significant effect (p < 0.05) on organoleptic attributes, antioxidant activity, and protein content, but did not significantly affect moisture content. Therefore, the A3B1 formulation is considered the most optimal, as it produced chocolate edamame jelly candy with good nutritional quality and high consumer acceptability.
uploud by Tedyy_14.04.2026
Keywords: jelly candy; gelatin; konjac powder; organoleptic; antioxidant activity.